Pseudomonas stutzeri MJL19, a rhizosphere‐colonizing bacterium that promotes plant growth under saline stress - Lami, María Jesús (2020)
Aims: The aim of this study was to find and use rhizobacteria able to confer plants advantages to deal with saline conditions. Methods and Results: We isolated 24 different bacterial species from the rhizosphere of halophyte plants growing in Santiago del Estero, Argentina salt flat. Four strains were selected upon their ability to grow in salinity and their biochemical traits associated with plant growth promotion. Next, we tested the adhesion on soybean seeds surface and root colonization with the four selected isolates. Isolate 19 stood out from the rest and was selected for further experiments. This strain showed positive chemotaxis towards soybean root exudates and a remarkable ability to form biofilm both in vitro conditions and on soybean roots. Interestingly, this trait was enhanced in high saline conditions, indicating the extremely adapted nature of the bacterium to high salinity. In addition, this strain positively impacted on seed germination, plant growth and general plant health status also under saline stress. Conclusions: A bacterium isolate with outstanding ability to promote seed germination and plant growth under saline conditions was found. Significance and Impact of the Study: The experimental approach allowed us to find a suitable bacterial candidate for a biofertilizer intended to alleviate saline stress on crops. This would allow the use of soil now considered inadequate for agriculture and thus prevent further advancement of agriculture frontiers into areas of environmental value.